Dysphonia and Cystic Fibrosis. (2nd September 2014) - Willis, John; Misono, Stephanie; Michael, Deirdre D.
Abstract : Objectives: Because cystic fibrosis transmembrane conductance regulator (CFTR) chloride channels are found in human vocal fold epithelium, we aimed to (1) assess the prevalence and severity of dysphonia in patients with cystic fibrosis (CF) and (2) compare these with control patient populations. Methods: Voice samples and the Voice Handicap Index‐10 (VHI‐10) were collected from patients with cystic fibrosis and control patients with and without chronic sinusitis. Voice samples underwent consensus auditory‐perceptual evaluation of voice (CAPE‐V) assessment by blinded speech‐language pathologists. Sinus‐related symptoms were assessed using the SinoNasal Outcome Test (SNOT‐20). Statistical analysis was performed using unpaired t‐tests and one‐way analysis of variance (ANOVA). Results: Thirty‐seven patients participated, including 17 with CF, 10 with chronic sinusitis, and 10 healthy controls. Prevalence of dysphonia by VHI‐10 criteria was 41% in CF, 20% in chronic sinusitis, and 0% in healthy controls. CF patients had worse VHI‐10 scores than healthy controls ( P =. 001). There was no significant difference in VHI‐10 or SNOT‐20 between CF and chronic sinusitis patients, but on CAPE‐V assessment, patients with CF had greater overall severity of dysphonia and strain compared with control patients with and without chronic sinusitis ( P <. 001) and ( P =. 022). Conclusions: Auditory‐perceptual evaluation demonstrated greater severity of dysphonia in patients with cystic fibrosis than in controls. This may identify an area of clinical need as well as an opportunity for improved understanding of the role of CFTR in human voice.